Eosinophil Count Variation among Histopathological Features of Appendectomy Specimens at Birat Medical College Teaching Hospital - Kafle, Santosh Upadhyaya; Singh, Mrinalini; Kafle, Neeta; Sinha, Amrita (Birat Journal of Health Sciences, 2020)
Introduction: The histopathological examination of appendectomy specimens is the gold standard method for diagnosis. The presence of eosinophil besides other inflammatory cells like neutrophils and mature lymphocytes within different histological layers of appendectomy specimens are common findings for labeling it under various groups. This finding supports the assumption that appendicitis is triggered by Type 1 hypersensitivity reaction. Objective: To evaluate the eosinophil count variation in appendectomy specimens in patients with the clinical diagnosis of appendicitis. Methodology: This is a cross sectional hospital based study of 144 appendectomy specimens obtained in Department of Pathology, Birat Medical College Teaching Hospital from January 2019 to December 2019. Socio-demographic data, association of histopathological patterns with age groups, gender and eosinophil count in various histopathological groups was compared and cross-tabulated using SPSS version 16. Result: Among 144 appendectomy specimens, male gender (50.70%) of 15-24 years age group (36.80%) was predominant. The commonest histopathological diagnosis was acute appendicitis (31.25%) with highest eosinophil count in all of its histological layers. The association of various histopathological patterns with age groups and gender were not statistically significant, whereas it revealed statistically significant correlation between eosinophil counts in all histological layers. Conclusion: Findings suggest that the eosinophil count variation in the entire histological layers correlate well among different histopathological patterns of appendectomy specimens. This reflects the high diagnostic value of evaluating the eosinophil count in appendectomy specimens.